Is Labor Green?: A Cross-National Panel Analysis of Unionization and Carbon Dioxide Emissions. Issue 1 (1st March 2019) - Alvarez, Camila Huerta; McGee, Julius Alexander; York, Richard
Abstract : In this article, we assess whether unionization of national workforces influences growth in national carbon dioxide (CO2) emissions per capita. Political-economic theories in environmental sociology propose that labor unions have the potential to affect environmental conditions. Yet, few studies have quantitatively assessed the influence of unionization on environmental outcomes using cross-national data. We estimate multilevel regression models using data on OECD member nations from 1970 to 2014. Results from our analysis indicate that unionization, measured as the percentage of workers who are union members, is negatively associated with CO2 emissions per capita, even when controlling for labor conditions. This finding suggests that unionization may promote environmental protection at the national level.